Math riddle for year 6 - Azman, Muhammad Alif; Ahmad, Muhammad Azirul Aziq; Roslan, Muhammad Firdaus Alif; Sachin, . (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Math puzzles offer a distinct approach to practicing mathematics compared to traditional questions. Unlike specific topic-based problems, puzzles often lack clear indications of the required skills. They challenge students to determine their own solution strategies instead of following predefined steps. Puzzles extend advanced students beyond grade-level content without widening curriculum gaps. Most importantly, they provide a glimpse into real-world math applications, allowing practice of important standards and fostering critical thinking and problem-solving skills essential for practical use. This system is targeted to students out there. They can be anywhere and anytime to enhance their ability in math. Math riddles enhance concentration and comprehension by developing the ability to decipher text beyond basic literacy. Reading between the lines, considering context, and comprehending multiple layers of meaning are essential skills that riddles help students cultivate.